The role and status of women in social work education: past and future considerations. - Bent-Goodley TB; Sarnoff SK (Journal of Social Work Education)
Survival is not an academic skill. It is learning how to stand alone, unpopular and sometimes reviled, and how to make common cause with those others identified as outside the structures in order to define and seek a world in which we can all flourish. It is learning how to take our differences and make them strengths.